An assessment of clinical pathways and missed opportunities for the diagnosis of nodular melanoma versus superficial spreading melanoma. (12th November 2015) - Cicchiello, Mark; Lin, Matthew J; Pan, Yan; McLean, Catriona; Kelly, John W
Abstract: Background: Missed opportunities in the diagnosis of nodular melanoma (NM) carry high prognostic penalties due to the rapid rate of NM growth. To date, an assessment of the pathways to diagnosis of NM versus superficial spreading melanoma (SSM) specifically comparing numbers of opportunities missed to undertake biopsy has not been performed. Methods: A retrospective questionnaire of 120 patients (60 NM patients, age and sex matched to 60 SSM patients) from the Victorian Melanoma Service (VMS) database was undertaken to assess pathways to diagnosis. The numbers of opportunities missed to undertake a biopsy and doctor behaviour at such encounters were recorded. Diagnostic delay (overall, patient's and doctor's delay) in terms of time was assessed. Results: Significant differences in opportunities missed to make a diagnosis of NM compared to SSM were found. In all, 43% of NM were biopsied at a first encounter compared to 70% of SSM. All SSM were diagnosed within three reviews. Overall, 33% of NM required at least three and up six reviews until biopsy. Patients with NM were more likely than those with SSM to be reassured that their lesions were benign. No significant differences in terms of time delay to diagnosis between NM and SSM were found. Conclusions: NM contributes disproportionately to melanoma mortality in Australia. Addressing earlier diagnosis of NM with renewed focus may make the biggest impact on the overall mortality of melanoma. The message that a period of observation is not appropriate for patients re‐presenting with lesions of concern must be more effectively communicated.